Analysis of the Role of Peripheral Ligands Coordinated to ZnII in Enhancing the Energy Barrier in Luminescent Linear Trinuclear Zn‐Dy‐Zn Single‐Molecule Magnets. Issue 44 (11th September 2015) - Costes, Jean Pierre; Titos‐Padilla, Silvia; Oyarzabal, Itziar; Gupta, Tulika; Duhayon, Carine; Rajaraman, Gopalan; Colacio, Enrique
Abstract Three new Dy complexes have been prepared according to a complex‐as‐ligand strategy. Structural determinations indicate that the central Dy ion is surrounded by two LZn units (L2− is the di‐deprotonated form of the N2O2 compartmental N, N′‐2, 2‐dimethylpropylenedi(3‐methoxysalicylideneiminato) Schiff base. The Dy ions are nonacoordinate to eight oxygen atoms from the two L ligands and to a water molecule. The Zn ions are pentacoordinate in all cases, linked to the N2O2 atoms from L, and the apical position of the Zn coordination sphere is occupied by a water molecule or bromide or chloride ions. These resulting complexes, formulated (LZnX)‐Dy‐(LZnX), are tricationic with X=H2O and monocationic with X=Br or Cl. They behave as field‐free single‐molecule magnets (SMMs) with effective energy barriers (Ueff) for the reversal of the magnetization of 96.9(6) K with τ0=2.4×10−7 s, 146.8(5) K with τ0=9.2×10−8 s, and 146.1(10) K with τ0=9.9×10−8 s for compounds with ZnOH2, ZnBr, and ZnCl motifs, respectively. The Cole–Cole plots exhibit semicircular shapes with α parameters in the range of 0.19 to 0.29, which suggests multiple relaxation processes. Under a dc applied magnetic field of 1000 Oe, the quantum tunneling of magnetization (QTM) is partly or fully suppressed and the energy barriers increase to Ueff=128.6(5) K and τ0=1.8×10−8 s for 1, Ueff=214.7 K and τ0=9.8×10−9 s for 2, and Ueff=202.4 K and τ0=1.5×10−8 s for 3. The two pairs of largely negatively charged phenoxido oxygen atoms with short DyO bonds are positioned at opposite sides of the Dy3+ ion, which thus creates a strong crystal field that stabilizes the axial MJ=±15/2 doublet as the ground Kramers doublet. Although the compound with the ZnOH2 motifs possesses the larger negative charges on the phenolate oxygen atoms, as confirmed by using DFT calculations, it exhibits the larger distortions of the DyO9 coordination polyhedron from ideal geometries and a smaller Ueff value. Ab initio calculations support the easy‐axis anisotropy of the ground Kramers doublet and predict zero‐field SMM behavior through Orbach and TA‐QTM relaxations via the first excited Kramers doublet, which leads to large energy barriers. In accordance with the experimental results, ab initio calculations have also shown that, compared with water, the peripheral halide ligands coordinated to the Zn2+ ions increase the barrier height when the distortions of the DyO9 have a negative effect. All the complexes exhibit metal‐centered luminescence after excitation into the UV π–π* absorption band of ligand L2− at λ=335 nm, which results in the appearance of the characteristic DyIII (4F9/2→6HJ/2; J=15/2, 13/2) emission bands in the visible region.